Sertraline-Induced Tics: A Case Report and Narrative Review. - Arasu, Ramesh; Badeshae, Semran; Furlong, Yulia; Chen, Wai (2022)
This brief report describes the case of a 16-year-old girl who was commenced on sertraline for anxiety and depression, and subsequently developed severe and debilitating motor tics. Cessation of sertraline was associated with the resolution of tics; after this, paroxetine was trialled and well tolerated with good response of targeted symptoms and without re-emergence of tics. A narrative literature review yielded a retrospective observational study and eight single case reports on selective serotonin receptor inhibitor-induced motor tics (three in adolescents and five in adults). Tics are not commonly considered as a side-effect of SSRIs. This case report is novel is several aspects: the tics emergence was immediate whereas previous cases were delayed; the tics symptoms were measured and quantified by a validated scale; a dose-response relationship was observed; to our knowledge, our case was the first adolescent female reported; and finally, paroxetine was well-tolerated as a substitute, although it is unclear whether the observed tics-sparing effect is co-incidental, ideocratic or can be replicated.